The Experience of HIV-Positive Transgender Women Engaging in Physical Activity: An Interpretative Phenomenological Analysis - Gilles de la Londe, Julie; Aïm-Eusébi, Amélie; Cadwallader, Delphine; Rincon Murillo, Giovanna; Cadwallader, Jean Sébastien; Aubert, Jean Pierre (Archives of sexual behavior, 2023)
Regular physical activity should benefit HIV-positive transgender women because they are a particularly vulnerable population. However, engaging in physical activity seems particularly difficult among this population. To inform the development of interventions to increase adherence to physical activity, we explored perceptions of physical activity in 10 semi-structured interviews with HIV-positive transgender women. Interviews were subjected to a qualitative approach named interpretative phenomenological analysis (IPA). Inspired by Cooley’s theory, we chose to illustrate the results according to a three-level structure, i.e., confronting oneself to oneself with a specific identity, then confronting oneself with others on an interpersonal level, and eventually confronting oneself with society as a normative frame through the specific prism of physical activity, and thus relationship to one’s body. The idea of practicing physical activity meant for them: having to face what they tried to be kept hidden, being ostracized by the cis population, and facing social heteronormativity. The fears about health were mostly about HIV and the transitioning process side effects. The psychological issues were mostly about the fear of developing male shaped bodies and worsened by traumatic life stories. External factors were often related to the passing concept and violence caused by stigma and discrimination. The group appeared as a strong motivation factor, facilitating self-acceptance and socialization.